2017
DOI: 10.1111/nyas.13406
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter fetus impairs barrier function in HT‐29/B6 cells through focal tight junction alterations and leaks

Abstract: Infections by Campylobacter species are the most common foodborne zoonotic disease worldwide. Campylobacter jejuni and C. coli are isolated most frequently from human stool samples, but severe infections by C. fetus (Cf), which can cause gastroenteritis, septicemia, and abortion, are also found. This study aims at the characterization of pathological changes in Cf infection using an intestinal epithelial cell model. The Cf-induced epithelial barrier defects appeared earlier than those of avian Campylobacter sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Apoptosis and tight junction alterations are important mechanisms through which intestinal microbes invade the hosts [39]. In our study, we observed higher activity of apoptosis after CLP.…”
Section: Discussionsupporting
confidence: 60%
“…Apoptosis and tight junction alterations are important mechanisms through which intestinal microbes invade the hosts [39]. In our study, we observed higher activity of apoptosis after CLP.…”
Section: Discussionsupporting
confidence: 60%
“…In our co-culture, C. jejuni provoked paradoxical upregulation of claudin-1 (Claudin-1 paradox); that is, upregulation of the barrier-forming TJ protein claudin-1 while epithelial resistance was reduced, which we explained by the re-distribution of claudin-1 off the tight junction domain [6]. Claudin-1 induction has also been observed before in human colon biopsies after C. jejuni infection [6], C. fetus or C. coli infection in HT-29/B6 cells [31], and pro-inflammatory cytokine stimulation in HT-29/B6 cells [32,33]. A correlation between increased claudin-1 protein expression and apoptosis induction also occurs in HT-29/B6 cells [34].…”
Section: Discussionmentioning
confidence: 85%
“…We also observed a claudin-1 upregulation in C. jejuni infection, the claudin-1 paradox, claudin-1 increase while the TER is decreased, as also shown before for C. fetus and C. jejuni in vivo. (Bücker et al, 2017(Bücker et al, , 2018Lobo de Sá et al, 2019). The overall increase of claudin-1 was associated with retraction of the protein from tight junction strands and localization in the basolateral membrane and intracellular compartments during the infection (Bücker et al, 2018).…”
Section: No Downregulation Of Barrier-relevant Tight Junction Proteinsmentioning
confidence: 93%